Faecal Calprotectin Is a Very Reliable Tool to Predict and Monitor the Risk of Relapse After Therapeutic De-escalation in Patients With Inflammatory Bowel Diseases. (6th February 2019) - Buisson, Anthony; Mak, Wing Yan; Andersen, Michael J; Lei, Donald; Kahn, Stacy A; Pekow, Joel; Cohen, Russel D; Zmeter, Nada; Pereira, Bruno; Rubin, David T
Abstract: Aims: To assess faecal calprotectin [Fcal] levels before and after therapeutic de-escalation, to predict clinical relapse in patients with inflammatory bowel disease [IBD]. Methods: From a prospectively maintained database, we enrolled 160 IBD patients [112 Crohn's disease/48 ulcerative colitis] in clinical remission, with Fcal measured within 8 weeks before therapeutic de-escalation. Clinical relapse was defined using the Harvey-Bradshaw index or Simple Clinical Colitis Activity Index. Results: Using a receiver operating characteristic [ROC] curve, Fcal >100 µg/g was the best threshold to predict clinical relapse after therapeutic de-escalation (area under the curve [AUC] = 0.84). In multivariate analysis, clinical remission >6 months before therapeutic de-escalation (hazard ratio [HR] = 0.57 [0.33–0.99]; p = 0.044) was associated with decreased risk of relapse, whereas current steroid medication ( = 1.67[1.00–2.79]; p <0.0001) was a risk factor. Fcal >100 µg/g was predictive of clinical relapse (HR = 3.96 [2.47–6.35]; p < 0.0001) in the whole cohort but also in patients receiving anti-tumour necrosis factor [TNF] agents [ n = 85 patients; p <0.0001], anti-integrins [ n = 32; p = 0.003], or no biologics [ n = 43; p = 0.049], or attempting to discontinue steroids [ n = 37; p = 0.001]. One patient [1/98] and seven patients [7/88, 8.0%] with baseline Fcal <100 µg/g relapsed within 3 months and 6 months after therapeutic de-escalation, respectively. A total of 74 Fcal measurements were performed in 52 patients after therapeutic de-escalation. Monitoring Fcal >200 µg/g [ROC curve with AUC = 0.96] was highly predictive of clinical relapse in multivariate analysis ([HR = 31.8 [3.5–289.4], p = 0.002). Only two relapses [2/45, 4.4%] occurred within 6 months while Fcal <200 µg/g. Conclusions: Fcal level is highly accurate to predict and monitor the risk of relapse after therapeutic de-escalation in IBD patients and could be used in daily practice.